APPLICATION OF COOPERATIVE LEARNING MODEL BASED ON ENVIRONMENT TO IMPROVE SOFT SKILLS AND LEARNING ACHIEVEMENTS (Study in Student Biology Subjects Class X at SMK Negeri 4 Lebong) - Meilinda Meilinda; Johanes Sapri (DIADIK, 2019)
This study aims to describe the improvement of soft skills and learning achievement of X Pharmacy class students by using an environment- based cooperative learning model in Biology subjects at SMK Negeri 4 Lebong. This study is a Classroom Action Research. The subjects of this study were 29th grade Pharmacy students of SMK Negeri 4 Lebong which consisted of 29 people consisting of 5 male students and 24 female students. Whereas, the object in this study is soft skills and student learning achievement on Biology subjects conducted through an environment-based cooperative learning model. Retrieval of research data using observation and test sheets. The results of this study indicate that the application of environment-based cooperative learning models can improve soft skills and student achievement in each cycle. On average the soft skills of students in the pre cycle, cycle I, and cycle II were 35.29% respectively; 54.74%; and 66.03%. The percentage of students' mastery learning in the pre cycle, cycle I, and cycle II were 55.17%; 75.86%; and 89.66%. The improvement data then proves that the application of environment-based cooperative learning models can improve soft skills and student achievement in Biology subjects at SMK Negeri 4 Lebong.